Hyperwriting, a multiscale writing with the method of loci - Aberkane, Idriss (Sens public)

(untitled) (Département des littératures de langue française, 2016)
Let us suppose that any media is the outsourcing of a mental function ; writing, then, is the outsourcing of working memory. For Dehaene and others, writing is a neural recycling by which populations specialized in form recognition are associated with sounds, thus forming a simple grapheme-phoneme association. Could there be other forms of writing then, or “neowriting”, and could they externalize other mental functions, such as say, episodic memory ? Here I propose a multiscale form of symbolic writing based on the method of loci, consisting of a loceme-noeme association endowed with a proto-grammar, which purpose is to externalize episodic memory, and allow for the mapping of noems onto space. I add that hyperwriting is not the only possible form of neowriting, thus posing the problem of the neuroergonomic optimality of existing media depending on their contents and cognitive purpose, and discuss its epistemological continuity with hypertext.